A relação semântica entre linguagem verbal e não verbal em tiras, com base na semântica argumentativa (The semantic relation between verbal and nonverbal language in comic strips based on the argumentative semantics) - Graeff, Telisa Furlanetto; Gomes, Lauro (Estudos da Língua(gem), 2015)
Com base em princípios e conceitos da Teoria Argumentativa da Polifonia, este trabalho propõe-se verificar se a relação de sentido existente entre linguagem verbal e não verbal, no gênero textual tira, é comandada pelo linguístico. Para tanto, construiu-se, a partir dos enunciados de duas tiras, as matrizes de sentido que compreendem o conteúdo argumentativo, a atitude do locutor frente ao conteúdo e a pessoa responsável pelo conteúdo. Verificou-se que o sentido dos quadrinhos que contêm apenas linguagem não verbal está previsto na linguagem verbal, pela sua relação com os aspectos argumentativos do bloco semântico que a linguagem verbal permite evocar. PALAVRAS-CHAVE: Argumentação. Enunciação. Linguagem verbal. Linguagem não verbal. ABSTRACT Based on principles and concepts especially of the Argumentative Theory of Polyphony, this study aims to verify if the meaning relation between verbal and nonverbal language, in the comic strip textual genre, is controlled by the linguistic. For that, there has been built up, in two comic strips, the matrix of sense of the utterances which comprises the argumentative content, the speaker’s attitude about the content and the person who is responsible for the content. It could be verified that the meaning of the comic strips that contain only nonverbal language is foreseen in the verbal language, by its relation with the argumentative aspects of the semantic block which the verbal language allows to evoke. KEYWORDS: Argumentation. Enunciation. Verbal language. Nonverbal language.